Evaluation of Potential Toxic Elements in Soils from Three Urban Areas Surrounding a Steel Industrial Zone - Georgios Charvalas; Aikaterini Molla; Alexios Lolas; Elpiniki Skoufogianni; Savvas Papadopoulos; Evaggelia Chatzikirou; Christina Emmanouil; Olga Christopoulou (Toxics)
The urban zone around the city of Volos, a Greek city with a historically industrialized profile, faces threats arising from Potential Toxic Element (PTE) contamination. The scope of this study is to determine the contamination levels of 10 PTEs in three urban areas which are located near the industrial zone in the city of Volos. For this purpose, a total of 30 soil samples from parks, playgrounds and roadsides were collected from the Agios Georgios, Velestino and Rizomilos areas (Magnesia, Central Greece). The sampling was conducted in June 2022 and the concentrations of chromium (Cr), nickel (Ni), copper (Cu), arsenic (As), cadmium (Cd), lead (Pb), iron (Fe), manganese (Mn), cobalt (Co) and zinc (Zn) were measured through inductively coupled plasma mass spectrometry (ICP-MS). The Contamination Factor (CF), Pollution Load Index (PLI) and Geo-accumulation Index (Igeo) revealed moderate pollution in most cases, whereas in some sites the contamination was significant for Ni or for As. Principal Component Analysis showed concomitant changes for some PTEs in Component 1 and for others in Component 2, explaining approximately 67% of the variation. K-means Cluster Analysis showed two distinct groups of PTE-impacted sites within these urban areas. It can be postulated that industrial activities may have a carry-over effect on the soil in residential areas. Frequent monitoring of areas deemed as “contaminated” and time-series data are needed to examine in depth the soil pollution in cities and its possible shifts in relation to the changes in industrialization status in the extended urban areas.